Studentsâ€™ Environmental Awareness and Practices: Basis for Development of Advocacy Program - Cruz, Jenny Perez; Tantengco, Nerissa S (Universitas Pendidikan Indonesia, 2017)
ABSTRACT: The descriptive study was used to identify the environmental awareness and practices of the selected students at the Sta. Elena High School in the Philippines. Findings revealed that based on the responses in the modified Environmental Awareness Scale, the respondents were moderately aware of the environmental concepts. In the participation in environmental programs, the respondents sometimes do the tasks of recycling; water and energy conservation; non-use of harmful products; creative possible solution; and social media solution. They seldom do the tasks of participating in tree planting and joining in schoolâ€™s environmental clubs. Studentsâ€™ interview revealed that in spite of the almost the same programs about environmental care cited by the officers of the different school clubs, not all of their schoolmates had initiatives in keeping the school campus clean. Through the guidance of their parents, the students participate in environmental practices at home. Accordingly, the teachers should strengthen the integration of environmental concepts, principles, and practices in various subjects in the school. KEY WORD: Awareness; Environmental Awareness Scale; Environmental Advocacy Program; Environmental Problems; Social Media.Â ABSTRAKSI: â€œKesadaran dan Pengamalan Siswa tentang Lingkungan: Dasar untuk Pengembangan Program Advokasiâ€. Kajian deskriptif ini digunakan untuk mengidentifikasi kesadaran dan praktek siswa terpilih di SMA (Sekolah Menengah Atas) Sta. Elena, Filipina. Temuan mengungkapkan bahwa berdasarkan tanggapan dalam Skala Kesadaran Lingkungan yang dimodifikasi, para responden cukup sadar akan konsep lingkungan. Dalam partisipasi program lingkungan, para responden kadang-kadang melakukan tugas-tugas daur ulang; konservasi air dan energi; tidak menggunakan produk yang berbahaya; solusi sekreatif mungkin; dan solusi media sosial. Mereka jarang melakukan tugas partisipatif dalam penanaman pohon dan bergabung di klub lingkungan sekolah. Para siswa mengungkapkan bahwa meskipun ada program yang hampir sama tentang perawatan lingkungan yang ditekankan oleh petugas dari klub sekolah yang berbeda-beda, tidak semua siswa sekolah memiliki inisiatif dalam menjaga lingkungan sekolah yang bersih. Melalui bimbingan orang tua, para siswa berpartisipasi dalam praktek menjaga lingkungan di rumah. Karena itu, guru harus memperkuat integrasi konsep lingkungan, prinsip, dan praktek dalam berbagai mata pelajaran di sekolah. KATA KUNCI: Kesadaran; Skala Kesadaran Lingkungan; Program Advokasi Lingkungan; Masalah Lingkungan; Media Sosial.Â Â About the Authors: Jenny Perez Cruz is the Araling Panlipunan (Social Studies) Department Coordinator of Sta. Elena High School at present in the Philippines. Nerissa S. Tantengco, Ph.D. is a Full Professor VI in the College of Teacher Development, Faculty of Behavioral and Social Sciences PNU (Philippine Normal University) in Manila, Philippines. Corresponding authors: tantengco.ns@pnu.edu.phHow to cite this article? Cruz, Jenny Perez Nerissa S. Tantengco. (2017). â€œStudentsâ€™ Environmental Awareness and Practices: Basis for Development of Advocacy Programâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.2(1) March, pp.43-64. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online).Chronicle of the article: Accepted (September 19, 2016); Revised (January 19, 2017); and Published (March 30, 2017).